MODEL LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PERILAKU PROSOSIAL SISWA - Yohana Touwe (Institut Agama Kristen Negeri (IAKN) Ambon, 2020)
The purpose of this study was to produce an effective group guidance service to improve students' prosocial behavior. This research design uses a Research & Development approach. The research and development method is a research method used to produce certain products and to test the effectiveness of these products, with a sample of 10 students selected by purposive sampling from 75 populations. A sampling of 10 students, so that in the process of giving treatment in group guidance activities is effective.The results of the study indicate that group guidance services to improve prosocial behavior have been achieved. This can be seen from the acquisition of prosocial behavior scores on the pretest and post-test which has increased by 234.6%. The effectiveness of this model was tested by using the Wilcoxon test in the Test Statistics table to obtain the Asymp value. Sig. (2-tailed) = 0.005 < = 0.05, then reject Ho. This means that the group guidance service model can improve the prosocial behavior of the students of SMA Negeri 1 Seram Barat.